The Nunarssuit intrusive complex South Greenland. Part 1: General description - Harry, W. T.; Pulvertaft, T. C. R. (Meddelelser om Grønland, 1963)
The Nunarssuit complex intrudes the pre-Cambrian basement of South Greenland. Measuring 45 X 25 km it appears to be the largest pluton in the Gardar Alkaline Province; abundance of augite syenite is an outstanding feature. Although the complex has not previously been the subject of a detailed study it has been taken in the past as providing evidence for ’transformist’ views. In fact, however, it presents the features of an igneous intrusion and metasomatic replacement of older rocks was not important in its formation. The boundary between the complex and the basement is highly discordant and it abruptly truncates the numerous Gardar dykes in the basement. Stoping of large blocks seems to have been the main means of emplacement: ring fracture, if operative, was unimportant. The chief members of the complex are as follows. The Alángorssuaq Gabbro has a roughly arcuate outcrop mainly comprising unaltered olivine gabbro, uralitized gabbro, and various hybridized rocks formed under the influence of later granites. The Helene Granite is clearly later than the gabbro and has much in common with the Scandinavian rapakivis: disintegration to ’moro’; occurrence of quartz in two generations; accessory fluorite; scarcity of pegmatites and of preferred mineral orientation. ’Rapakivi’ mantled K felspar ovoids are, however, lacking. The granite is remarkably homogeneous considering its areal extent. For the most part it is a coarse-grained rock chiefly consisting of perthite mainly as subrectangular crystals 2-3 cm long, and quartz. Green hornblende and pale-green clinopyroxene are the common coloured minerals but fayalite and biotite can occur. The Kitsigsut Syenite resembles the larvikites of the Oslo region though its felspars are not usually schillerized. It includes a dark variety essentially consisting of perthite with some pale-green or -brown augite and olivine, and a pale variety in which the felspars tend to be highly exsolved. The Biotite-Granite, a stock-like body, contains both microcline perthite and oligoclase or albite. Biotite is the chief dark mineral. There is some evidence that the Biotite-Granite is slightly younger than the Helene Granite and it is undoubtedly younger than the gabbro and Kitsigsut Syenite. The Nunarssuit Syenite, a large monotonous mass of pyroxene-fayalite syenite, resembles the Kitsigsut Syenite although apatite is not a common accessory and quartz often occurs in small amounts. Towards much of its contact with the Helene Granite and to ·some extent against the basement it passes into a marginal finer-grained quartzose phase. Other varieties of minor extent occur within the intrusion. The Kitdlavât Granite laccolith and various small bodies of aenigmatite-bearing soda-granites were later intruded into the syenite. The Nunarssuit Syenite is younger than the Helene Granite; in parts of Nunarssuit, however, the Helene Granite veins the syenite and was probably not completely consolidated at the time of the syenite emplacement. The Malenefjeld Granite, a large independent mass of soda-granite, is nowhere seen in contact with the main body of the complex but is plainly part of the latter. Xenoliths are uncommon in the complex as a whole but are abundant at certain localities, the most significant being a zone that approximately coincides with the boundary between the Nunarssuit Syenite and Helene Granite in western Nunarssuit. The inclusions in this and two other eastward-dipping zones in S.W. Nunarssuit are largely metavolcanic rocks derived from the Kobberminebugt green schists and measure up to 100 m in thickness. Many are lenticular: these lie with their lengths in the plane of the zones. It seems likely that they are the remnants of roof-pendant wedges disrupted more or less in situ. Unlike the Julianehåb Granite and green schist country rocks of the complex the xenoliths have often suffered high-grade thermal metamorphism. Mafic mineral layering is well-developed at certain places in the complex. In the gabbro it can be concordantly accompanied by felspar lamination and is inclined towards a focus in the interior of the complex. In the Helene Granite it is highly localized: remarkable sequences resembling the trough banding of Skærgaard occur and another type involves textural variants of the granite as well as mafic bands; there are also planar successions and isolated bands in which cumulus fayalitic olivine is common. More or less planar rhythmic sequences generally unaccompanied by mineral parallelism are extensive in the Kitsigsut Syenite; as in the Helene Granite layering, grading and cross-bedding can be present. Some banding also occurs in the Biotite-Granite and Kitdlavât Granite. In the Nunarssuit Syenite mafic layering is mainly confined to three zones in S.W. Nunarssuit. These and the remaining occurrences are inclined towards a focus in central Nunarssuit. Numerous spectacular structures faithfully mimic primary sedimentary features such as crossbedding, wash-outs, slumping and graded bedding. The mafic layers are concentrations of cumulus minerals formed under the influence of gravity in a cooling magma-chamber. Magmatic currents were also effective in most intrusions, particularly the Nunarssuit Syenite. Their activity indicates a high degree of mobility in the magmas concerned and this may be connected with the fluorine content of the complex.